Strategi Memperkuat Branding Dalam Menghadapi Citra Buruk Perusahaan Pialang (Sosialisasi Ke Masyarakat) - Nadya Puspita Wardhani; Sulastri Irbayuni (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
This outreach activity to the community aims to build a brokerage company image branding strategy. Brokerage companies often face challenges in maintaining a positive image amidst negative perceptions that arise due to various issues and scandals involving the corporate industry. A bad image of a brokerage company can damage investor confidence and hinder long-term business growth. In Indonesia, there are still many people who do not understand investment principles. Seeing the existing problems, this community service activity provides insight and understanding for the community through training as part of the branding strategy. Participants can also have the opportunity to play golf while sharing. Thus, the insights gained by SSC participants "Sharing Cari Cuan" are not only material on how to invest, but also get other experiences from community service activities carried out.